Hearing Aid Outcome Measures and Auditory Processing in Elderly Users of Binaural Amplification - Niloofarsadat Fatemi; Mohammad Ebrahim Mahdavi; Hamid Jalilvand; Alireza Akbarzadeh Baghban (Auditory and Vestibular Research)
Background and Aim: Generally, peripheral hearing loss in the elderly is associated with decreased auditory processing ability. Researchers have drawn attention to the role of auditory processing in the success of hearing amplification. The present study investigates the relationship between auditory processing and benefit and satisfaction of binaural hearing aids in the elderly. Methods: Forty-seven elderly users (aged 58–85 years) of binaural hearing aids, all of whom exhibited symmetrically mild to moderate sensory-neural hearing loss, completed the questionnaires of International Outcome Inventory for Hearing Aids (IOI-HA) and Abbreviated Profile of Hearing Aid Benefit (APHAB) and the Persian version of Words-in-Noise (WIN) and two-pair Dichotic Digits (DD) tests. Results: Signal-to-Noise Ratio-50% (SNR-50) and Non-Dominant Ear Score (NDES) collectively explained 16% of the binaural hearing aid benefit variance. NDES accounted for 14% of the variance observed in satisfaction. Conclusion: Binaural hearing aid benefit and satisfaction in the elderly were not similarly related to auditory processing abilities. NDES alone is a weak but significant predictor of satisfaction and in combination with WIN SNR-50 is a moderate predictor of benefit.